Social networks, University Teaching and Spanish Baroque Sculpture. Reflections and possibilities from educational innovation - Sánchez López, Juan Antonio; Fernández Paradas, Antonio Rafael (Historia y Comunicación Social, 2014)
Social networks are emerging from educational innovation context as potential resources. For this reason Social networking can be a powerful tool for knowledge of specific university subjects such as Spanish Baroque Sculpture.